The Dopamine Allosteric Agent, PAOPA, Demonstrates Therapeutic Potential in the Phencyclidine NMDA Pre-clinical Rat Model of Schizophrenia - Daya, Ritesh P.; Bhandari, Jayant; Kooner, Sharnpreet K.; Ho, Joella; Rowley, Christopher D.; Bock, Nicholas A.; Farncombe, Troy; Mishra, Ram K. (Frontiers in Behavioral Neuroscience, 2018)
PAOPA, a potent analog of Prolyl-Leucyl-Glycinamide, has shown therapeutic potential at the preclinical stage for dopaminergic related illnesses, including animal models of schizophrenia, Parkinson’s disease and haloperidol-induced extrapyramidal movement disorders. PAOPA’s unique allosteric mechanism and dopamine D2 receptor specificity provide a unique composition of properties for the development of potential therapeutics for neuropsychiatric illnesses. We sought to investigate PAOPA’s therapeutic prospects across the spectrum of schizophrenia-like symptoms represented in the established phencyclidine-induced rat model of schizophrenia, (5 mg/kg PCP twice daily for seven days, followed by 7 days of drug withdrawal). PAOPA was assessed for its effect on brain metabolic activity and across a battery of behavioural tests including, hyperlocomotion, social withdrawal, sensorimotor gating, and novel object recognition. PAOPA showed therapeutic efficacy in behavioural paradigms representing the negative (social withdrawal) and cognitive-like (novel object recognition) symptoms of schizophrenia. Interestingly, some behavioural indices associated with the positive symptoms of schizophrenia that were ameliorated in PAOPA’s prior examination in the amphetamine-sensitized model of schizophrenia were not ameliorated in the PCP model; suggesting that the deficits induced by amphetamine and PCP—while phenotypically similar—are mechanistically different and that PAOPA’s effects are restricted to certain mechanisms and systems. These studies provide insight on the potential use of PAOPA for the safe and effective treatment of schizophrenia.